Falling through the Cracks: Deaf New Americans and Their Unsupported Educational Needs - Michael A. Schwartz; Brent C. Elder; Monu Chhetri; Zenna Preli (Education Sciences, 2022)
Members of the Deaf New American community reported they arrived in the United States with no formal education, unable to read or write in their native language, and had zero fluency in English. Efforts to educate them have floundered, and the study aims to find out why and how to fix the problem. Interviews of eight Deaf New Americans yielded rich data that demonstrates how education policy in the form of the Individuals with Disabilities Education Act (IDEA) and other laws fail to address their needs, because these laws do not include them in their coverage. The study’s main findings are the deleterious effect of the home country’s failure to educate their Deaf citizens, America’s failure to provide accessible and effective instruction, and the combined effect of these institutional failures on the ability of Deaf New Americans to master English and find gainful employment. This article is an argument for a change in education policy that recognizes the unique nature of this community and provides for a role of Deaf educators in teaching Deaf New Americans.